A variant of KCC2 from patients with febrile seizures impairs neuronal Cl− extrusion and dendritic spine formation. (25th March 2014) - Puskarjov, Martin; Seja, Patricia; Heron, Sarah E; Williams, Tristiana C; Ahmad, Faraz; Iona, Xenia; Oliver, Karen L; Grinton, Bronwyn E; Vutskits, Laszlo; Scheffer, Ingrid E; Petrou, Steven; Blaesse, Peter; et al.
Synopsis <boxed-text content-type="graphic" id="embr201438749-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> A missense mutation of the K‐Cl co‐transporter KCC2, identified in patients with febrile seizures, leads to defects in neuronal Cl− extrusion and dendritic spine formation in vivo and in cultured cells. A rare SLC12A5 variant with an arginine‐to‐histidine substitution at position 952 in the KCC2b isoform is identified in an Australian family with early childhood onset of febrile seizures. Expression of the KCC2‐R952H variant leads to reduced Cl− extrusion, cortical dendritic spine formation and surface expression of the KCC2b protein. The significant functional deficits taken together with the low genetic tolerance of SLC12A5 are consistent with a role for KCC2‐R952H as a susceptibility gene in febrile seizures.